Dust Flow Separator Type Electrostatic Precipitator For A Control Of Particulate Matter Emissions From Natural Gas Combustion - Guan, Lili (My University, 2005)
Pollution problems have drawn worldwide awareness and become significantly important now. Particulate matter (PM) emission is one of the key pollution issues. Particulate matter has a significant impact on the environment and human health, especially particle sizes that range below lOJJ.m. Researches continuously work an improvement of fine particulate matter collections emitted from all kinds of sources, such as automobiles, industrial combustion, etc. Governments in many countries are planning to regulate the PM emission from the existing PM10 (particle diameter<10μm) to new limits PM2.5 (particle diameter<2.5μm) within the next few years. For this reason, present PM control system needs to be improved.
The objective of this work is to develop a dust flow separator type electrostatic precipitator (DFS-ESP) for the effective control of fine particulate matter emission from natural gas combustions. The characteristic of PM emitted from natural gas combustion is studied, and the performance of a DFS-ESP is evaluated by experiments and numerical predictions.
An experiment was conducted for natural gas combustion exhaust flow rates from 2.5 to 9 Nm^3/h, ESP applied voltages from 0 to 30kV, and gas temperature from 80 to 160°C. A series of particle measurements were conducted at upstream, downstream and middle of the DFS-ESP system by an optical particle counter for particle mass density, and by condensation nucleate particle counter for particle size distributions and particle number density. Particle sampled from the natural gas combustion system was also analyzed by an environmental scanning electron microscope (ESEM) technique. Flow velocity profile and pressure drop of the DFS-ESP were measured by a Pitot tube and diaphragm type pressure transducer, respectively.
The experimental results show that the particle size emitted from natural gas combustion ranges from 17 to 300nm in diameter, and the volume density is approximately from 5 x 10^8 #pt/m^3 to 5 x 109 #pt/m^3 depending on the combustion conditions. The dust flow separator can concentrate 90% of fine particles in 1 to 3% of the gas flow and divert it from the main flow to the ESP section where the particles can be removed. In terms of overall particle collection efficiency, the DFS-ESP system can remove up to 90% of the particles based on the number density. The pressure drop across the DFS-ESP is observed to be lower than lPa for the present range of flow rate, which is within acceptable limits for industrial applications.
Keywords: Dust Flow; Flow Separator; Electrostatic Precipitator; Particulate Matter; Natural Gas; Combustion